The heavyweight championship - Ryan, Pat. (Mankato, MN : Creative Education, 1993)
Describes significant moments in the history of the heavyweight boxing championship.
Keywords: Boxing -- History -- Juvenile literature; Boxers (Sports) -- Biography -- Juvenile literature; Boxing -- History